Investors with the Golden-I: preference in Gold-I investment / Zaimy Johana Johan. - Johan, Zaimy Johana (Universiti Teknologi MARA Selangor, 2020)
The gold price has risen recently after the United States implemented a drastic monetary action by reducing the interest rate to almost zero to cushion the effect of Covid-19 pandemic on the economy. However, what has triggered the gold price could be beyond Covid-19. Therefore, this study examines the factors influencing customers' preference in gold investment (Gold-i). Applying a purposive sampling technique; 100 out of 110 questionnaires were usable and further analysed using SPSS v. 22.Two variables; inflation and income growth are significant while the interest rate is not significant with Gold-i preference. Since interest raterelates to the strength of US Dollar, central bank reserves and investment demand, it could be postulated that during the study in 2019, interest rate and the gold price had risen in tandem. This research further enrichesknowledge and contributes to the advancement of research in goldinvestment, hence enabling researchers, bankers, investors, tradepolicymakers to understand further the investment in Gold-i duringeconomic crises, in particular the current recession triggered by theCovid-19 pandemic.